Markers of thrombin and plasmin generation in patients with inherited thrombophilia. Issue 7 (July 1994) - Lee, L H; Jennings, I; Luddington, R; Baglin, T
Abstract : AIM--To determine the prevalence of a biochemically detectable hypercoagulable state, defined in terms of increased thrombin or plasmin generation, in patients with phenotypically characterised thrombophilia. METHODS--Plasma concentrations of the prothrombin activation peptide F1.2 and fibrin degradation (FbDP) and fibrinogen degradation products (FgDP) were measured by enzyme immunoassay in 104 patients deficient in natural anticoagulants, and 35 unaffected relatives. RESULTS--Increased concentrations of F1.2, FbDP, and FgDP were present in 18, 25, and 19 of 104 patients, respectively. There were no correlations between F1.2, FbDP, and FgDP concentrations, or between these parameters and concentrations of natural anticoagulants except for a negative correlation between protein C concentrations and FgDP (rho = -0.46, p = 0.009). CONCLUSION--A biochemically detectable hypercoagulable state is present in some patients with asymptomatic thrombophilia. Markers of plasmin generation may be increased more frequently in thrombophilia than markers of thrombin generation. This finding should prompt the inclusion of markers of plasmin generation in prospective longitudinal cohort studies to determine the predictive value of a hypercoagulable state, defined by either excessive thrombin or plasmin generation, for the development of venous thromboembolism.